Ethics, health policy-making and the economic crisis: a qualitative interview study with European policy-makers - Caroline Brall; Peter Schröder-Bäck; Rouven Porz; Farhang Tahzib; Helmut Brand (BMC, 2019)
Abstract Background The economic crisis posed various challenges to policy-makers who had to decide on which health policy measures to focus on and on which to refrain from. The aim of this research was to assess the relevance of ethics and to highlight ethical dimensions in decision-taking by policy-makers with regard to policy and priority-setting in health systems posed by the economic crisis. Methods Semi-structured qualitative interviews were conducted with eight European policy-makers from six countries. Results All interviewees recalled difficult and strenuous situations where they had to prioritise between distinct areas to focus on and invest in, for example around choices between prioritising medications, health professional staffing, care specific equipment, or urgent infrastructure issues. Values could be identified which they deemed as important within the policy-making process, such as trust and responsibility. They explicitly expressed the need for ethical tools and assistance in terms of policy advice for reaching morally sustainable decisions in health policy matters. Conclusions The study showed that ethical concepts and values frequently come into play in health policy-making, and that ethics is highly relevant in policy-makers' daily decision-taking, yet that they lack ethical guidance on what to base their decisions. The study is of relevance since it can provide future decisions on austerity-related issues with an ethical underpinning and could identify areas of moral concern.